Evidence of the Uyunbulak Salt Lake Water Recharge in the Kumish Basin, Xinjiang, China, from Boron Isotopes - Xuehai Ma; Yunqi Ma; Huaide Cheng; Changzhong Li; Huanen Gu; Haiyun Zhang; Qingyu Hai (Geofluids)
The reserves of nitrate (NO3-) mineral resources in the Turpan-Hami Basin in Xinjiang rank second after those in the Atacama Desert in Chile, South America. Considerable attention has been devoted to nitrogen (N) sources of NO3- deposits in recent years due to the increase in demand for NO3- fertilizers in agriculture and chemical industries. However, although the potassium nitrate (KNO3) deposits in the Uyunbulak salt lake in the Kumish basin, Xinjiang, China, have received increasing attention from numerous researchers in recent years, they all focused on the study of nitrate sources and agreed that the nitrate source in the Kumish basin is mainly atmospheric sedimentation. Studies on their water sources are scarce; for salt lake nitrate deposits, water supply also plays a crucial role in the genesis of the deposit. As a sensitive indicator, a boron isotope is often used to indicate water bodies from different sources. However, the presence of NO3- ions in water will interfere with the determination of boron isotopes, so the research on boron isotopes in nitrate salt lakes has been hindered. In this study, the three-step ion exchange method published by Ma et al. (2020) was used to eliminate the influence of NO3- ions in water on boron isotope determination, so as to reveal the water supply of Uyunbulak Salt Lake in Kumish basin by using boron isotopes which are more sensitive to water types. In this study, ice and snow meltwater, fissure water, groundwater, and surface water samples were collected from the Kumish basin and analyzed for the determination of boron (B) isotopic and hydrochemical compositions during the migration process of water bodies to reveal the recharge relationship between the water bodies from the northwestern margin of the basin and the study area. The obtained hydrochemical composition results showed a gradual increase in the salinity of the water body from 556 to 7372 mg/L from the northwestern to the southeastern parts of the basin, resulting in a gradual change in the hydrochemical facies type of Uyunbulak salt lake to NaCl. This finding suggested that the water body migrates from the northwestern to southeastern parts of the basin. The results of B isotope composition indicated two types of water bodies from different sources, namely, the ice and snow meltwater of the Southern part of the Tianshan Mountains and groundwater of the basin, exhibiting B isotope composition ranges of 26.66–27.26‰ and 12.75–15.19‰, respectively. These two types of water bodies are mixed at the Uzong spring (Q1). The ice and snow meltwater in the mixed water accounted for 46%, while the groundwater accounted for 54%. The mixed water continues to recharge the Uyunbulak Salt Lake in the southeastern part of the basin.